A concepção de legitimidade do poder em Rousseau - Rosa, Marlene de Fátima (2014)
The present research paper has as an objective the investigation of the political power s legitimacy in the works of Jean-Jacques Rousseau. In his reflections Rousseau tries to understand the shaping of the political powers that took place in the West, recovering all of mankind s history in a hypothetical way to demonstrate how mankind s progress has contributed to put men in the condition of misery and servitude that they now live in. In his studies, the author expresses his way of interpreting the power that has been establishing and characterizing itself in the societies of his time. Rousseau shows that the construction of his thought towards the model of society was originated from many sources, from the observation of the political institutions of his time to the study of authors such as Grotius, Pufendorf, Hobbes, Montesquieu, Locke, Machiavelli and others. In his investigations, Rousseau innovates the kinds of political and social interpretation, indicating new perspectives to understand these areas. His analysis intends to show his understanding of man and society, having as a starting point, firstly, anapproach around the problem of inequality, and secondly, showing his notion towards the kinds of power that constituted themselves throughout mankind s history. Following this historical path, he presents these two characteristics and how they influenced each other.In other words, how the power constituted itself illegitimately through the existing inequalities since its constitution. Following his reflections, Rousseau describes how these illegitimate kinds of power can assume other setups and become legitimate through an administrative rule that allows the accomplishment of popular sovereignty. The comprehension of the legitimating elements of this new administrative rule is what we intend to investigate based on the arguments presented by Rousseau.